New Faunistic Records of Tiger Moths (Lepidoptera, Arctiidae, Arctiinae) in West Pakistan - Gurko, V.O.; Inayatullah, M.; Mashwani, M.A. (Вестник зоологии, 2011)
Four species were collected in Balochistan Province: Axiopoena maura (Eichwald, 1830), Lacydes incurvata (Ebert, 1973), Utetheisa pulchella (Linnaeus, 1758) and Nebrarctia transversa (Moore, 1879). L. incurvata is recorded from Pakistan for the first time. Distribution and systematic position of all mentioned species are discussed. На территории Пакистана (провинция Белуджистан) собраны четыре вида медведиц: Axiopoena maura (Eichwald, 1830), Lacydes incurvata (Ebert, 1973), Utetheisa pulchella (Linnaeus, 1758) и Nebrarctia transversa (Moore, 1879). L. incurvata для территории Пакистана приводится впервые. Уточнены ареалы распространения вышеупомянутых видов и их систематическая принадлежность.